Association of Interfacility Helicopter versus Ground Ambulance Transport and in-Hospital Mortality among Trauma Patients. (31st August 2021) - Stewart, Kenneth; Garwe, Tabitha; Oluborode, Babawale; Sarwar, Zoona; Albrecht, Roxie M.
Abstract: Background: Relatively few studies have compared outcomes between helicopter transport (HT) and ground transport (GT) for the inter-facility transfer of trauma patients to tertiary trauma centers (TTC). Mixed results have been reported from these studies ranging from a slight increase in odds of survival for the severely injured to no evident benefit for HT patients. We hypothesized there was no adjusted difference in mortality between patients transported interfacility by HT or GT taking into account distance from TTC. Methods: Data from an inclusive statewide trauma registry was used to conduct a retrospective cohort study of adult (18+ years old) trauma patients who initially presented to a non-tertiary trauma center (NTC) before subsequent transfer by HT or GT to a TTC. Records from the NTC and TTC were linked (N = 9880). We used propensity adjusted, multivariable Cox proportional hazards models to assess the association of HT on mortality at 72-hour and within the first 2 weeks of arrival at a TTC; these multivariable analyses were stratified by distance (miles) between NTC and TTC: 21-90, and greater than 90. Results: Mean distance between NTC and TTC was greater for HT patients, 96.7 miles versus 69.9 miles for GT. A higher proportion of patients among the HT group had an ISS of 16 or higher (24.6% vs 10.9%), an initial SBP < 90 mmHg (7.3% vs 2.8%), and GCS < 10 (12.5% vs 3.7%) than the GT group. HT was associated with significantly decreased 72-hour mortality (HR 0.65, 95%CI 0.48-0.90) for patients transferred from a NTC <90 miles from the TTC. No association was seen for patients transferred more than 90 miles to the TTC. No significant association of HT and 2-week mortality was seen at any distance from the TTC. Conclusions: Only for patients transferred from an NTC <90 miles from the receiving TTC was HT associated with a significantly decreased hazard of mortality in the first 72 hours. Many HT patients, especially from the most distant NTCs, had minor injuries and normal vital signs at both the NTC and TTC suggesting the decision to use HT for these patients was resource-driven rather than clinical.